The degree of use of distance education in the schools of the Mafraq Kasbah from the teacher’s perspective - Almashakbeh, Rania Reda (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the degree of use of distance education in the schools of the Mafraq Kasbah from the teacher’s perspective. To achieve the goal of the study, the descriptive developmental method is used, The study population consisted of all teachers of the schools of the Directorate of Education for the Mafraq district for the academic year 2020/2021, and a questionnaire consisting of (21) items, Divided into three areas (teachers, students, parents), and its validity and reliability were confirmed, and then it was distributed to the study sample consisting of (320) male and female teachers. They were chosen randomly. The results of the study on the degree of use of distance education in the schools of the Mafraq Kasbah from the teacher’s perspective were moderate, on the total domain with an arithmetic mean (2.82), which was high on the domain of teachers, medium on the domain of students, and low on the domain of parents. The results of the study also showed that there were statistically significant differences in the estimates of the study sample members of the degree of using distance education in the schools of the Mafraq district in Jordan, according to the gender variable on all fields and on the tool as a whole and in favor of males. To the degree of using distance education in the schools of the Mafraq district in Jordan, according to the variable of the study stage in all fields and on the tool as a whole and in favor of the basic stage. In light of the results of the study, the researcher recommended the necessity of holding specialized training courses in distance education for teachers and administrators, employing the Ministry of Education in the Mafraq district to follow up education through educational platforms and promoting their use, and providing special requirements for distance education for teachers and students as much as possible.